Dry Heating of Cowpea Flour below Biopolymer Melting Temperatures Improves the Physical Properties of Bread Made from Climate-Resilient Crops - Stefano Renzetti; Ine Heetesonne; Ruth T. Ngadze; Anita R. Linnemann (Foods, 2022)
Improving the technological functionality of climate-resilient crops (CRCs) to promote their use in staple foods, such as bread, is relevant to addressing food and nutrition security in Africa. Dry heating of cowpea flour (CPF) was studied as a simple technology to modulate CPF physicochemical properties in relation to bread applications. For this purpose, the melting behavior of cowpea starch and proteins in CPF was first studied and modeled using Flory–Huggins theory for polymer melting. Next, dry-heating conditions were investigated based on the predicted biopolymer melting transitions in CPF to be well below starch and protein melting. The pasting properties (i.e., peak viscosity, final viscosity, breakdown and setback) of CPF could be selectively modulated depending on temperature-time combinations without altering the thermal behavior (i.e., melting enthalpies) of CPF. Water-binding capacity and soluble solids decreased with the increased severity of the temperature-time combinations. Dry-heated CPF added to CRC-based bread significantly improved crumb texture. In particular, dry heating at 100 °C for 2 h provided bread with the highest crumb softness, cohesiveness and resilience. The positive effects on the crumb texture could be largely related to enhanced starch integrity, as indicated by a reduction in breakdown viscosity after treatment. Overall, dry heating of CPF under defined conditions is a promising technology for promoting the use of CPF as a techno-functional and protein-rich ingredient in bread-type products.